Teleology of bioecotoximonitors in aquatic ecotoxicology - Argota-Pérez, George (2023)
The search for biotools for the assessment of the environmental quality of aquatic ecosystems is a priority. Bioindicators and biomonitors are adequate for judgment, but not excellent in controlling multiple biases on ecotoxicological predictions. The objective was to describe the teleology of bioecotoximonitors in aquatic ecotoxicology. The teleology of bioecotoximonitors is based on a pyramid that guides the identification of ecosystem service importance, guidance on damage consequences, differential significance between one resource and another, as well as the need to apply assessments with bioecotoximonitors towards understanding the dynamics of ecosystem processes. The explanatory use towards the existential applicability of natural conditions, and in this case of the contamination of aquatic ecosystems, is what is relevant in the teleology of bioecotoximonitors. It is concluded that the teleology of bioecotoximonitors in aquatic ecotoxicology enables the measurement of the least amount of biases, the selective explanation of which would be essential in the applicational understanding.